Floaters as coach`s joker? Effects of the floaters positioning in 3vs3 small-sided games in futsal. - Pizarro, D.; Práxedes, A.; Travassos, B.; Gonçalves, B.; Moreno Domínguez, A. (International Journal of Performance Analysis in Sport, 2021)
The aim of this study was to analyse the effects of floater positioning within futsal Gk+3vs3+Gk SSGs on youth players` tactical and physical performance. An independent measure approach under four experimental conditions was carried out: Floaters Off (FO), Goal Line Floaters (GLF), Lateral Floaters own court sidelines (LFocsl) and Lateral Floaters full court sidelines (LFfcsl). Thirty male futsal players (U19 age category) participated in the study. Players` activity was assessed using WIMU PROTM and heart rate (HR) was recorded by HR monitors during the SSGs. Results showed significant differences in the physical variables (p = 0.05), not finding such differences in the tactical variables analysed. However, significant differences were observed in relation to the spatial occupation areas. GLF is related to higher distance and speed variables, being the most demanding SSG; in LFocsl, lower HR values were obtained, and FO is linked to the acceleration and deceleration variables, being an indicator of futsal performance. These findings should be considered for the design of futsal training tasks, according to the context (team, players …) and time of the week and the season, since they allow the development of the variables described by optimising training time with the ball.